2010
DOI: 10.1007/s10856-010-4120-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel thin-walled nerve conduit with microgrooved surface patterns for enhanced peripheral nerve repair

Abstract: Randomly aligned nerve cells in vitro on conventional culture substrata do not represent the complex neuronal network in vivo and neurites growing in uncontrolled manner may form neuroma. It is of great importance to mimic the organised growth pattern of nerve cells in the study of peripheral nerve repair. The aim of this work was to modify and optimize the photolithographic technique in creating a reusable template in the form of a silicon wafer that could be used to produce contact guidance on biodegradable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Control films were also prepared on a smooth silicone substrate, whereby the flat uppermost surface of the film resulted in a micropitted conformation. 5 …”
Section: Film Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Control films were also prepared on a smooth silicone substrate, whereby the flat uppermost surface of the film resulted in a micropitted conformation. 5 …”
Section: Film Preparationmentioning
confidence: 99%
“…4 We have previously reported that ultrathin PCL films and PCL/PLA blended films with a micropitted surface are able to support the attachment and growth of the NG108-15 neuronal cell line and Schwann cells. 5 Schwann cells are key players in nerve regeneration through delivery of neurotrophic factors and extracellular matrix proteins; however, the absence of Schwann cells in a nerve gap has led to much current work being focused on the use of stem cells to deliver this. We have previously demonstrated that PCL films can support adipose-derived stem cells (ASCs), differentiated to a Schwann cell-like phenotype (dASC), as a potential tissue-engineered route to nerve repair.…”
mentioning
confidence: 99%
“…In particular, textures can be used to control optical properties, [35] to tailor how liquid spread on surfaces or flow within channels, [36,37] and to influence how cells grow and nerves regenerate. [38][39][40] The fabrication of fibers with sub-micrometer textures that could exhibit such advanced…”
mentioning
confidence: 99%
“…Cells are distinctly responsive to every cue in their environment including surface topography, stiffness, and interacting fi ber diameter and change their behavior accordingly (Georges and Janmey 2005 ;Pedersen and Swartz 2005 ;Khatiwala et al 2006 ;Curtis and Riehle 2001 ). Grooves, micro-and nanofi bers, gels, and fi lms have been studied in order to promote and direct neuronal outgrowth and enhance neuronal attachment (Xie et al 2010 ;Sun et al 2010 ;Mobasseri et al 2013 ;Daud et al 2012 ;Bell and Haycock 2012 ). Instead of using hollow guidance tubes that lacks physical properties of the native nerve structure, studies have focused on developing materials that guide the axons to the distal site of the injury.…”
Section: Engineering Topographical and Mechanical Properties For Neurmentioning
confidence: 99%